Studi Morfologi Enterobius Vermicularis Menggunakan Preparat Mikroskopis Dari Kasus Anak 3-10 Tahun Di Persisir Pantai - Aldiana Astuti; Ni Ketut Yuliana Sari; Agnes Rantesalu; Marni Tangkelangi; Novian Aghni Yudhaswara (Lembaga Pengembangan Kinerja Dosen, 2025)
Enterobius vermicularis, or pinworm, continues to be a public health concern, particularly among children in coastal and densely populated areas. Though it is classified as a non-Soil Transmitted Helminth (non-STH), its fecal-oral transmission route allows rapid spread, especially where hygiene practices are inconsistent. In Indonesian coastal communities such as Lasiana, Kupang, limited studies have focused on the intersection between environmental factors, personal hygiene, and parental knowledge in relation to enterobiasis. This study aimed to determine the prevalence and morphological characteristics of Enterobius vermicularis in children aged 3–9 years living in the coastal area of Lasiana Beach, Kupang. A descriptive observational study was conducted involving 81 heads of households and 24 children as research participants. Data were collected through questionnaires distributed to parents to assess sanitation conditions, hygiene practices, and knowledge levels. Perianal samples were obtained from the children using the clear tape (scotch tape) method and examined microscopically to identify E. vermicularis eggs. Findings revealed that 21% of the children tested positive for E. vermicularis. The eggs displayed typical morphological features—oval shape with one flattened side and a transparent double-layered shell. Despite most respondents reporting good hygiene behavior and environmental sanitation, cases of infection persisted. Limited access to handwashing facilities and dense housing conditions were identified as contributing risk factors. The presence of Enterobius vermicularis infections despite adequate sanitation and knowledge highlights a gap between awareness and effective daily practices. These findings underscore the need for strengthened community-based health education and consistent monitoring in high-risk coastal areas to prevent enterobiasis among children.